Proximal tibia modular endoprosthetic replacement. Analysis of complications - Vyrva, Oleg; Skoryk, Ivan; Shevchenko, Igor; Malyk, Roman; Golovina, Yanina; Mikhanovskiy, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The reconstruction of proximal tibial by using modular endoprosthetics is a complex surgical procedure, accompanied by a significant number of complications (40–70 %) in the period of follow up of 5–15 years. Objective: to analyze the primary complications of modular endoprosthetic reconstruction of proximal tibial. Methods: the results of surgical interventions performed on 47 patients with PT tumor lesions (20 men (42.6 %) and 27 women (57.4 %), age from 12 to 74 years) were evaluated. The patients were divided into two groups: I (35 people) — primary modular endoprosthetics after removal of the tumor, II (12) — revision. Results: in the period from 3 weeks to 13 years after the establishment of a modular endoprosthesis due to complications, 18 (38.2 %) patients underwent revision surgeries. The implanted endoprosthesis was removed in 12 cases (25.5 %): in group I — 9 (25.7 %), in II — 3 (25 %). Due to tumor recurrence, 2 (4.26 %) myofascioplastic amputations were performed. Complications associated with the insufficiency of soft tissues (type I) were observed in 3 (6.3 %) people: in group I — 1 (7.6 % of all complications in the group), in II — 2 (40 %). Aseptic instability (type II) was detected in one case of group I (7.6 % of all group complications) 6 years after primary endoprosthesis. Periprosthetic infection (type IV) developed in periods from 12 days to 4 years in 12 patients (70 % of all complications): in group I — 9 (52.9 %), in II — 3 (17.6 %). Local recurrence of a tumor lesion (V type) was detected in 2 (11.7 % of all complications) people of group I after 6 months. and 3 years after surgery. Conclusions: in patients with malignant tumors of proximal tibial, the technique of replacing post-resection defects with modular endoprostheses is justified, since it provides 61.8 % positive results.